Combined infant massage and kangaroo mother care for weight gain in a low-birth-weight infant: A nursing case study - Regina Natalia; Filza Fadhila; Fasida Dharma Yudastoro (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Low-birth-weight infants are vulnerable to feeding difficulties, hypothermia, impaired growth, and nutritional problems because of physiological immaturity. Infant massage and kangaroo mother care are non-pharmacological nursing interventions that may support physiological stability, breastfeeding, and weight gain. Purpose: To describe the implementation of infant massage and kangaroo mother care in supporting weight gain in a low-birth-weight infant. Method: A nursing case study was conducted using the nursing care process. The participant was one clinically stable low-birth-weight infant with a nursing diagnosis of risk for nutritional deficit. Data were collected through nursing assessment, physical examination, observation, medical record review, and daily body-weight monitoring. Infant massage and kangaroo mother care were implemented according to hospital procedures during five days of hospitalization. Results: The infant’s body weight increased from 2,150 g to 2,300 g over five days. Improvement was also observed in sucking ability and general clinical condition. No adverse events related to the interventions were reported during the observation period. Conclusion: Infant massage and kangaroo mother care may support weight gain and clinical stability in low-birth-weight infants. However, findings from a single case should be interpreted cautiously, and further studies with larger samples and longer follow-up are needed.